Yoga and stress profile for women undergoing infertility treatment: review - Singh, Neeta; Rawat, Dimple; Akbar, Shahnaz; Yadav, Arun K.; Zangmo, Rinchen; Achra, Shalini; Sarkar, Avir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Infertility is a silent struggle rising rapidly. Women undergoing treatment for infertility experience tremendous stress not only emotionally but socially also. It has been hypothesized that stress can hamper fertility and studies indicate an effective role of yoga in reducing stress. Hence, the review aims to assess if yoga has an effect on stress levels in infertile women thus improving the clinical outcome. Present review was registered on Prospero prospectively (CRD42022336237). A review was carried out to summarize the interventions assessing role of Yoga in reducing stress among women undergoing infertility treatment. Literature search was performed using a pre-defined search strategy on PubMed, Embase, and CTRI along with a manual search of references during the last decade. A total of 2959 articles via database searching and 202 via manual and citation searching were screened. Only two studies were found relevant meeting the inclusion criteria. Three studies with a similar intervention were retrieved but had different study designs and outcomes. All studies supported the recommendation of yoga as a complementary intervention. The review concluded yoga may have the potential in reducing stress thus improving clinical outcomes and suggests Ayush to conceive and plan large scale RCTs on this area to see the effect on clinical outcome.